No Leaders/No Masses: Virtuality and Contemporary Group Life in the Shadow of Freud - Fernando Castrillón (EJP import test, 2021)
Summary: One hundred years ago, Freud traced an outline of power, group-cohesion, identification, and a form of the subjective/social bond. A century later, digital commodity capitalism and hyper-modernity have served to undermine the position and properties of both leader and masses, with a ubiquitous screen-mediated virtuality that requires a reformulation of Freud’s initial ideas on the subject. Towards that end, I will examine the “virtual” nature of the contemporary “leader”, a social-media composite best exemplified by the figure of Trump that is continually resurrected by QAnon followers. As well, I will analyze the “masses” or disparate conglomerations that are brought together by the virtual leader’s insistent “lifting of the veil,” a perverse articulation of statecraft endemic to our moment. I conclude with some considerations regarding what the next few years may have in store for us.[1]